Analisis Konsep Keselamatan Dalam Perspektif Reformed: Studi Sistematis Tentang Doktrin Sola Gratia (Jurnal Pendidikan Agama dan Teologi, 2025)
This journal examines the concept of salvation (soteriology) from the perspective of Reformed theology with a special focus on the doctrine of Sola Gratia. This research uses doctrinal and historical analysis methods to investigate the development of understanding of the gift of salvation from the time of the Reformation to contemporary interpretations. The research results show that the doctrine of Sola Gratia remains relevant in modern theological discourse and provides an important foundation for an understanding of salvation that is centered on God's sovereignty.